Teachers’ Perceptions of Artificial Intelligence Integration in Elementary School Learning: A Phenomenological Study - Foesti Nafasya; Fauzia Rahma Suci; Febriyanto Febriyanto; Safrizal Safrizal; Ratmiati Ratmiati (Institute of Research and Community Service STAI Yayasan Tarbiyah Islamiyah Kota Padang, 2026)
The development of Artificial Intelligence (AI) has brought significant changes to the world of education, including at the elementary school level. This study aims to describe and understand in-depth teachers' responses to the implementation of AI in the learning process in elementary schools, including their perceptions, experiences, challenges, and opportunities in utilizing AI technology. This study uses a qualitative approach with a phenomenological method, focusing on the subjective experiences of teachers as the main actors in the implementation of AI-based learning. The research subjects consisted of elementary school teachers who have used or are familiar with AI technology in learning activities. Data collection techniques were carried out through in-depth interviews, observation, and documentation. Data were analyzed using the stages of data reduction, data presentation, and conclusion to obtain the essential meaning of the teachers' experiences. The results show that most teachers responded positively to the implementation of Artificial Intelligence because it is considered to increase learning efficiency, help personalize materials, and foster student interest and motivation in learning. However, this study also found obstacles such as limited digital competence of teachers, lack of specialized training, and concerns about technological dependency and the ethical aspects of AI use in early childhood learners. The implications of this research indicate the need for policy support, improving teachers' digital literacy, and developing ethical and pedagogical guidelines for implementing AI in elementary schools to ensure its optimal use and alignment with educational goals.